Development of Educational Research on Integrated Combinatorial-Thinking learning model: Combinatorial thinking skills - Putra, Eric Dwi; Slamin; Kristiana, Arika Indah; Suwito, Abi (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to develop and test the ERIC (Educational Research on Integrated Combinatorial-Thinking) learning model to improve students' combinatorial thinking skills in mathematics learning. Using a Research and Development (R&D) approach modified from the Borg & Gall design, this study involved expert validation, limited trials, as well as analysis of the validity, practicality, and effectiveness of the model through a combinatorial thinking skills test and a student response questionnaire. The results showed that the ERIC model was valid, with an average score of 3.737 from three validators. The model's practicality was rated very good, with the implementation rate reaching 95.67% and student activity averaging 94.85%. The model's effectiveness can be seen from the students' achievement in combinatorial thinking, with the highest score on the indicator "identifying several problems" (98.33%). Student response to learning was also very positive, with 97.6% giving positive responses. The ERIC learning model integrates Problem-Based Learning (PBL) elements with combinatorial thinking indicators, creating a systematic, collaborative, and creative approach. This model improves students' ability to solve mathematical problems and prepares them to face real-world challenges more effectively and innovatively. The ERIC learning model can be implemented in mathematics learning to enhance students' combinatorial thinking skills, which are essential for solving complex problems and applying mathematical logic in real-life situations. Additionally, this approach helps lecturers guide students more effectively through discussion-based and collaborative learning strategies.